Who patronises Islamic banks in Indonesia? - Abduh, Muhamad; Omar, Mohd. Azmi (Centre for Islam and Social Sciences (CISS), 2010)
INTRODUCTION Indonesia is a country within the South East Asia region with the largest Muslim population in the world. It has a total population of 290 million, 80 percent or 232 million of them are Muslims. Although the number and proportion of Muslims is significantly large, however, it does not correspond to the share of Islamic banking assets vis a vis the total banking assets in the country 1 . History of Islamic banking in Indonesia began in 1992 when the government introduced Banking Act No. 7, which allowed banks to operate on Islamic principles. This led to the establishment of Bank Muamalat Indonesia in the same year. This development is actually ten years behind Malaysia and Turkey and almost twenty years behind Dubai that has established the first commercial Islamic bank in 1975 namely, Dubai Islamic bank. Table 1 shows that up to December 2009, there are 6 Islamic commercial banks (i.e., Bank Syariah Mandiri, Bank Muamalat Indonesia, Bank Syariah Mega Indonesia, BRI Syariah, BUKOPIN Syariah, and PANIN Syariah) with 711 branches and 25 conventional banks that have Islamic windows with 287 branches. The number of Islamic rural banks also increased significantly from 105 in 2006 to 138 in 2009. As a result, there are 1,223 branches of Islamic banks spread around Indonesia to meet the needs of Muslims in the country.